Crisis in the Philippines the Marcos era and beyond - Bresnan, John 1927-2006 (Princeton, N.J. Princeton University Press, 1986)
The book provides an overview of the history of the Philippines from the period of Spanish colonial domination to the present and analyzes the twenty-year Marcos record and the causes of the downfall of the Marcos regime. The essays will greatly aid the general reader in understanding the Philippine-American relationship. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press.
Philippine-American tensions in history / Theodore Friend -- Tradition and response / David Steinberg -- The social situation / Wilfredo F. Arce and Ricardo G. Abad -- Politics in the Marcos era / Lela Garner Noble -- The political crisis / Carl H. Lande -- The economic crisis / Bernardo Villegas -- Reconstituting the political order / Carolina G. Hernandez -- Economic relations / Jesus P. Estanislao -- Political and security relations / William J. Barnds.
Electronic reproduction.
Keywords: Marcos, Ferdinand Edralin -- 1917-1989.; Philippines -- History -- 1946-1986.; United States -- Relations -- Philippines; Philippines -- Relations -- United States